2023
DOI: 10.1007/s00535-022-01949-6
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and behavioral changes in Japanese patients with inflammatory bowel disease due to COVID-19 pandemic: a national survey

Abstract: Background Given the increasing health concerns for patients with inflammatory bowel disease (IBD), amidst the COVID-19 pandemic, we investigated the impact of the pandemic on the anxiety and behavioral changes in Japanese patients with IBD. Methods We analyzed 3032 questionnaires from patients with IBD, aged 16 years or older visiting 30 hospitals and 1 clinic between March 2020 and June 2021. The primary outcome was the score of the anxiety experienced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Patients with asymptomatic COVID‐19 may have been missed in this study. Third, several studies have shown the psychological impact of COVID‐19 in patients with chronic diseases, such as inflammatory bowel diseases 35–37 . However, no data are available on this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with asymptomatic COVID‐19 may have been missed in this study. Third, several studies have shown the psychological impact of COVID‐19 in patients with chronic diseases, such as inflammatory bowel diseases 35–37 . However, no data are available on this issue.…”
Section: Discussionmentioning
confidence: 99%
“…In a survey conducted with the support of the European Federation of Crohn's and Ulcerative Colitis Association, 4% of the respondents stopped using IBD medication during the pandemic on their own [52]. Nakase et al reported that only 0.6% of patients discontinued therapy, 1.9% used medications at reduced doses, and 97.5% used medications as directed [63]. These results suggest that good adherence is possible despite the ongoing disruptions caused by the pandemic.…”
Section: Impact Of the Covid-19 Pandemic On Medication Adherence In P...mentioning
confidence: 99%
“…When infection rate is high, medication adherence is assumed to decline because of hospitals being closed or people not being able to visit hospitals; however, in cases where an epidemic has subsided, adherence is assumed to decline because of worsening mental status or other factors. Nakase et al reported that the most common reasons for discontinuing medications were "stable abdominal symptoms" (38.4%), "instructions from the attending physicians" (31.5%), and "a higher risk of contracting infection due to medication" (21.9%) [63]. Although physicians should communicate with patients to help them understand the necessity of continuing medication therapy, only 7% of the patients reported discussing their medication with their medical staff during the pandemic [66].…”
Section: Impact Of the Covid-19 Pandemic On Medication Adherence In P...mentioning
confidence: 99%
“…According to a survey of inflammatory bowel disease patients, 56.2% of patients were afraid to go to the hospital for fear of contracting SARS-CoV-2. 11 Healthcare providers were also concerned about the spread of infection through hospital visits and allowed a certain amount of delay in visits if necessary. Indeed, the American Association for the Study of Liver Diseases, the European Association for the Study of the Liver, and the Asian Pacific Association for the Study of the Liver (APASL) recommended continued surveillance of patients at risk of developing cancer, with a 2-month delay if necessary.…”
Section: Introductionmentioning
confidence: 99%
“…At the outset of the COVID‐19 pandemic, patients may have been reluctant to visit hospitals for fear of SARS‐CoV‐2 infection. According to a survey of inflammatory bowel disease patients, 56.2% of patients were afraid to go to the hospital for fear of contracting SARS‐CoV‐2 11 . Healthcare providers were also concerned about the spread of infection through hospital visits and allowed a certain amount of delay in visits if necessary.…”
Section: Introductionmentioning
confidence: 99%